Topography-Guided Trans-Epithelial No-Touch Photorefractive Keratectomy for High Irregular Astigmatism After Penetrating Keratoplasty: A Prospective 12-Months Follow-Up - Spadea L; Visioli G; Mastromarino D; Alexander S; Pistella S (Dove Medical Press, 2021)
Leopoldo Spadea, Giacomo Visioli, Davide Mastromarino, Shehani Alexander, Santino Pistella Eye Clinic, Policlinico Umberto 1, "Sapienza" University of Rome, Rome, ItalyCorrespondence: Leopoldo SpadeaHead Eye Clinic, Policlinico Umberto 1, "Sapienza" University of Rome, Via Benozzo Gozzoli 34, Rome, 00142, ItalyTel +39 06 519 3220Fax +39 06 8865 7818Email leopoldo.spadea@uniroma1.itPurpose: To describe the efficacy and safety of topography-guided trans-epithelial no-touch photorefractive keratectomy (PRK) for the correction of highly irregular astigmatism after penetrating keratoplasty (PK).Patients and Methods: A prospective study was conducted on 12 eyes of 12 patients affected by highly irregular astigmatism after PK for keratoconus. Each patient underwent a single-step topography-guided trans-epithelial ablation (CIPTA® 2 software, iVis Technologies). Corneal topography data as well as uncorrected (UDVA) and corrected distance visual acuity (CDVA) and spherical equivalent (SEQ) were collected preoperatively (T0) and at 1 (T1), 3 (T2) and 12 (T3) months after surgery.Results: Mean UDVA and CDVA significantly improved, respectively, from 1.22± 0.17 and 0.18± 0.03LogMAR at T0 to 0.63± 0.17 (CI 95%, P< 0.001) and 0.04± 0.03LogMAR at T3 (CI 95%, P< 0.001). Mean SEQ significantly decreased from − 3.75± 1.32 to - 1.60± 1.32D (CI 95%, P< 0.02). Mean subjective refractive astigmatism (SRAST) and mean keratometry astigmatism (SimK) significantly decreased, respectively, from 7.83± 0.98 and 8.10± 1.48D to 2.83± 0.98 and 5.29± 1.48D (CI 95%, P< 0.001). Corneal Morphological Irregularity index (CMI) significantly decreased from 62.76± 7.26 μm to 23.24± 7.26 μm (CI 95%, P< 0.001). Apart from a single episode of graft rejection 5 days after ablation, successfully reverted with topical steroids, no other complications were noted. A mild corneal haze was observed in two eyes (16.7%) at 3 months post-PRK, and no regression was observed at 12 months.Conclusion: Our study demonstrates the safety and long-term effectiveness of a trans-epithelial topography-guided ablation in the treatment of post-PK highly irregular astigmatism.Keywords: PRK, corneal aberrations, keratoconus, refraction, corneal transplant